Contents : 3 projects - Mtongana, Lindile (Rhodes University, Faculty of Education, Department of Education, 1999)
This project comprises a case study that I conducted at New Horizon High School in Butterworth, a school with a good reputation for its excellent academic standard. It is about Staff Development, which I have identified as the most vital component of effective teaching. Although there is a need to ensure that there is an adequate supply of teachers in schools, the greatest challenge lies in the development of the quality of those who are already in service. This enormous challenge seems to have been forgotten by many school leaders. I hope this study will be beneficial to school principals and teachers who want to be successful in their teaching careers in the 21st century.
Keywords: Teachers -- In-service training; School management and organization -- Parent participation; Education and state -- South Africa; Educational law and legislation -- South Africa